Currently unavailable: until 09/08/2016
Degree: Mathematical Physics (Bachelors) - Edinburgh University
|Maths Higher Level||Baccalaureate||7|
|Physics Higher Level||Baccalaureate||7|
|English Literature Higher Level||Baccalaureate||7|
|Chemistry Higher Level||Baccalaureate||6|
|German Standard Level||Baccalaureate||7|
|Economics Standard Level||Baccalaureate||6|
|Before 12pm||12pm - 5pm||After 5pm|
Please get in touch for more detailed availability
The electron in a box model uses the idea that the energy of the electron and that of a standing wave in a box are analogous. So using your knowledge of standing waves you can derive an equation for the electrons energy.
The equation you need to derive is KE = (n2h2)/(8mL2)
It looks a little daunting and is not something I would memorise. Thankfully the derivation just requires 3 main steps and 3 main equations.
Treat the electron in a box as you would treat a standing wave on a string length L. The boundary conditions are that the wave has nodes at either end of the string. If you start drawing out the possible wavelengths on a string length L you will start to see a relationship emerging between the number of anti-nodes, n, and the wavelength, λ. Thus the allowed wavelengths are λ = 2L / n where n = 1, 2, 3, ...
Now that we have this relation we can use our equations from quantum physics, look for one that might includes λ, in this case λ = h / p.
Now substitue p = mv we have λ = 2L / n = h / (mv). Which rearranges to v = (hn) / (2Lm). So now we have an equation for the velocity of the electron in terms of L.
Remember we needed to find an expression for the energy, but there is the equation KE = mv2 / 2. So by substitution:
KE = (n2h2)/(8mL2)
This equation can model the energies of an electron according to it's energy level in the atom. So the n in the equation represents its energy level, the h is Planck's constant, m is the mass of the electron and L is the the length of the box or the space to which the electron is confined.see more
The integral of sine is pretty easy to remember as it is -cos + C. However you need to be able to prove this, without using the integral of cosine. This method uses sines exponential form.
As eiθ = cosθ + isinθ, sine can be expressed as sinθ = (eiθ- e-iθ) / 2i. This can make the integration easier as the indefinite integral of ekx = (1/k)ekx and the indefinite integral of e-kx = (-1/k)e-kx
Thus ∫sinx dx = ∫(eix- e-ix) / 2i dx = (1/2i)[ ∫eixdx - ∫e-ix dx] = (1/2i)[eix/i + e-ix/i] + C = [-(eix + e-ix) / 2] + C.
Now just as sine can be expressed using complex numbers so can cosine such that cosθ = (eiθ + e-iθ) / 2.
Thus ∫sinx dx = [-(eix + e-ix) / 2] + C = - cosx + Csee more